Assessing willingness to pay for Sharia general insurance in Indonesia: A case study of the Jabodetabek region - Rafidah Herawati; Irfan Syauqi Beik; Linda Karlina Sari (Faculty of Islamic Economics and Business, UIN Salatiga, 2024)
This study explores the willingness to pay (WTP) for Sharia general insurance in Jabodetabek, Indonesia, where adoption remains low. The objective is to assess how gender, residence, age, education, occupation, and income influence WTP. Using a quantitative approach, data were collected from 250 respondents through a structured questionnaire. The analysis involved descriptive statistics, cross-tabulation, and chi-square tests. Results indicate that gender, age, and income significantly affect WTP, with higher WTP observed among men, older individuals, and those with higher incomes. Conversely, residence, education, and occupation do not significantly impact WTP. The findings suggest that Sharia insurance providers should tailor products and educational efforts to better align with different demographic groups’ financial capabilities and needs. These insights are crucial for enhancing the adoption of Sharia general insurance in the region.